(untitled) (Cardiovascular Journal, 2010)
Background: Accurate diagnosis and clinical staging of heart failure (HF) is essential for its proper management and logical drug therapy to reduce morbidity and mortality. On this perspective researcher are in search of a good biomarker as complementary to the clinical parameters to improve the performance of HF diagnosis and its clinical staging. B-type natriuretic peptide (BNP) secreted by cardiac ventricles in HF has emerged as a new promising biomarker in this regard. Objective of the study was evaluation of plasma BNP concentration in relation to the severity of HF and its use as a biomarker for clinical staging of HF. Methods: In a cross sectional study 100 HF cases diagnosed by clinical parameters and echocardiography were enrolled and sub grouped into NYHA classes (I, II, II & IV) depending on clinical severity and functional limitations. Plasma BNP measured in all study subjects and summarized in each of these sub groups. Results: Median plasma BNP concentration in NYHA class-I, II, III & IV found to be 82.7, 267.2, 694.8 & 1530.4pg/ml respectively with progressive rising trend and at 95% CI level the plasma BNP in different sub groups were 64.5-112.7, 214.3-293.5, 626.4-902.4 & 1443.1-2384.4pg/ml respectively. Conclusion: Plasma BNP concentration increases progressively with increasing severity of HF to make it to be used for clinical staging of the disease. In mild, moderate and severe HF plasma BNP proposed to be 100-460, 460-1170 and >1170pg/ml respectively. Keywords: BNP; Heart failure; Biomarker. DOI: 10.3329/cardio.v2i2.6630 Cardiovasc. j. 2010; 2(2) : 142-146